Komunikasi Intrapersonal dalam Proses Penerimaan Diri Mahasiswi Korban Body Shaming - Insani, Mutiara Fitri; Yuliana, Nina (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Victims of body shaming who often receive negative comments and criticism by others through the intrapersonal communication process that occurs within themselves, whether it is talking to themselves or when observing and understanding the surrounding environment on an intellectual and emotional level, but it can also trigger feelings of lack of self-acceptance that have an impact on their daily lives and how they place themselves in the surrounding environment. However, there are also victims of body shaming who are able to accept themselves well, as evidenced by how they do not judge themselves negatively and choose to focus on the positive aspects of themselves. The purpose of this study is to understand how intrapersonal communication and self-acceptance process that body shaming victims go through. The research method used is phenomenology. Research on two female body shaming victims shows that the intrapersonal communication experienced consists of four stages, namely sensation, perception, memory, and thinking and produces feelings of shame and sadness. Both informants were also able to accept themselves through the stages of self-acceptance, namely denial, anger, depression, bargaining, acceptance.